Early renaissance in Italy (Northbrook, Ill. Roland Collection, 1986)
Features the following works of artists : Uccello, Masaccio, Masolino, Fra Angelico, Piero della Francesca, Filippo Lippi, Verrochio, Baldovinetti, Boticelli, Piero de Cosimo, Luca Signorelli, Andrea Mantegna, Antonello de Messina and Crivelli.
VHS format.
Director, Henry Lewes ; writer/narrator, Edwin Mullins.
Keywords: Art, Renaissance; Renaissance -- Italy